Method and device for recycling positive and negative electrode materials of waste lithium ion battery and product
By using eutectic salt with a density between the positive and negative electrode material between the positive and negative electrode materials of the used lithium-ion battery, the separation is achieved by heating, which solves the problem of separation of positive and negative electrode materials in the prior art, and achieves efficient and low-cost recycling and regeneration technology.
Patent Information
- Application Number
- CN202411868086.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-18
AI Technical Summary
The existing lithium-ion battery recycling process cannot effectively separate positive and negative electrode materials, resulting in complex recycling processes and waste of material value.
The eutectic salt with a density between the positive electrode material and the negative electrode material is mixed with the positive and negative electrode materials of the waste lithium-ion battery. The eutectic salt reaches the eutectic point by heating, so as to achieve separation and regeneration of the positive and negative electrode materials.
It realizes efficient separation and regeneration of positive and negative electrode materials, simplifies the recycling process, reduces costs, and improves the purity and recycling efficiency of the material.
Smart Images

Figure CN119725834A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of waste battery recycling, and more specifically, to a method, device and product for recycling positive and negative electrode materials of waste lithium-ion batteries. Background Art
[0002] Lithium-ion batteries dominate the energy storage and electrification fields due to their high power density and environmental protection. Shipments have continued to grow explosively in the past decade. Considering that the service life of lithium-ion batteries is usually less than ten years, their retirement wave is coming. Due to the fluctuation of material costs and the limited resources of key materials, lithium-ion batteries have serious material supply problems, especially positive and negative electrode materials, which account for a large proportion of the value. Therefore, there is an urgent need to develop efficient electrode material recycling and regeneration technology.
[0003] The recycling routes of hydrometallurgy and pyrometallurgy are cumbersome, have low return on investment, and produce secondary pollution, so they are not suitable for industrial production. Direct regeneration of LIBs electrode materials has attracted widespread attention due to its economic and environmental advantages. It can maintain its chemical structure while recycling electrode materials, and is expected to become the next generation of industrial application direction that meets the requirements of low energy consumption, economy and environmental protection. However, the premise of the conventional direct regeneration process is to target a single positive or negative electrode material, but what is actually obtained is usually a mixture of positive electrode material, negative electrode material and black powder. How to achieve the fine separation of positive and negative electrode materials is still a difficult problem in the industry. The inability to separate positive and negative electrode materials means that positive electrode materials can only be based on pyrometallurgical or hydrometallurgical technology, taking the technical route from "material" to "element", which greatly increases the recycling process and wastes the potential value of materials. Summary of the invention
[0004] In response to the defects of the prior art, the present application provides a method, device and product for recycling positive and negative electrode materials of waste lithium-ion batteries, aiming to solve the problem that the existing recycling process cannot separate the positive and negative electrode materials.
[0005] According to one aspect of the present application, a method for recycling positive and negative electrode materials of waste lithium-ion batteries is provided, which specifically comprises: S1 pre-treats the waste lithium-ion battery to obtain a mixed material of positive electrode material and negative electrode material, and then mixes the mixed material with a eutectic salt to obtain a mixture to be separated, wherein the density of the eutectic salt is 2.5 g / cm 3 ~3.5g / cm 3 within the scope of S2: heating the mixture to be separated to above the eutectic point of the eutectic salt, collecting the upper solid material to obtain the regenerated negative electrode material, and collecting the lower solid material to obtain the regenerated positive electrode material.
[0006] Through the above technical scheme conceived by the present application, compared with the prior art, the present application utilizes a eutectic salt with a density between that of the negative electrode material and the positive electrode material to directly separate and regenerate the positive and negative electrode materials, thereby realizing a recycling and regeneration technical route directly from "material" to "material", effectively simplifying the recycling process, and having the advantages of simple process and low cost.
[0007] As a further preferred embodiment, the cations in the eutectic salt include 5% to 35% of Li + The anions in the eutectic salt include more than 15% NO 3 - .
[0008] The present application optimizes the types and contents of cations and anions in the eutectic salt, thereby enabling simultaneous recovery and regeneration of positive and negative electrode materials in waste lithium-ion batteries, thereby further simplifying the recovery process.
[0009] As a further preference, the regenerated negative electrode material is collected by air flow suction combined with filtration.
[0010] As further preferred, in step S1, the waste lithium-ion batteries are pre-treated specifically by crushing the waste lithium-ion batteries and heating them at 300°C to 450°C for 0.5h to 1h, and then screening out flaky materials with a size greater than 20μm to obtain a mixed material of positive electrode materials and negative electrode materials.
[0011] As a further preferred embodiment, the cations in the eutectic salt further include 35% to 70% of density regulating cations, and the remainder are melting point cations, based on molar content, and the density regulating cations are alkali metal or alkaline earth metal ions with an atomic number greater than 40, such as Cs + , Ba 2+ One or more of the above, wherein the melting point adjusting cation is an alkali metal or alkaline earth metal ion with an atomic number less than 21, such as K + , Ca 2+ One or more of; the anions in the eutectic salt also include Br - ,I - OH - Medium ClO 4 - The reason why alkali metal and alkaline earth metal ions are preferred is that the outermost electron layers of the two metals have only 1 or 2 electrons, respectively, and the resulting salts are relatively stable, have less valence change, and are not easily decomposed by heat, thus reducing the occurrence of additional side reactions.
[0012] As a further preference, the mass proportion of the co-molten salt in the mixture to be separated is greater than 2 / 3.
[0013] As a further preferred embodiment, the regenerated negative electrode material is washed and placed in an inert atmosphere, and annealed at 700° C. to 900° C. for 1 h to 2 h to improve the charge and discharge cycle stability of the regenerated negative electrode material.
[0014] As a further preferred embodiment, the regenerated positive electrode material is washed and placed in an oxygen-containing atmosphere or an inert atmosphere, and annealed at 800° C. to 950° C. for 4 h to 8 h to improve the charge-discharge cycle stability of the regenerated positive electrode material. The ternary material and lithium cobalt oxide material are placed in an oxygen atmosphere, and the lithium iron phosphate material is placed in an inert atmosphere.
[0015] According to another aspect of the present application, a regenerated negative electrode material and / or a regenerated positive electrode material prepared by the above-mentioned recycling method is provided.
[0016] According to another aspect of the present application, a device for recovering positive and negative electrode materials of waste lithium-ion batteries is provided, the device comprising a separation unit and a negative electrode collection unit, the separation unit is used to contain a mixture to be separated obtained by mixing the positive and negative electrode materials of waste lithium-ion batteries with a eutectic salt, and to heat the mixture to be separated to above the eutectic point of the eutectic salt, so that the regenerated negative electrode material floats and the regenerated positive electrode material sinks; The negative electrode collection unit includes a transport pipeline, a collection bin, a filter membrane and an air suction pump. One end of the transport pipeline extends into the separation unit and is located above the liquid surface, and the other end extends into the collection bin. The outlet of the collection bin is provided with a filter membrane. The air suction pump is connected to the outlet of the collection bin, and the suction port of the air suction pump is located in the internal space of the filter membrane, so that the regenerated negative electrode material that is not infiltrated with the eutectic salt and floats on the surface can be collected by air suction.
[0017] In general, the above technical solutions conceived by this application have the following technical advantages compared with the prior art: 1. The recycling method provided in this application does not require the separation of positive and negative electrode materials in the crushing stage. It can separate and regenerate the positive and negative electrode materials of waste lithium-ion batteries in one step by using only a eutectic salt with a density between that of the positive electrode material and the negative electrode material. It has opened up a new recycling and regeneration technology route from "material" directly to "material", effectively simplified the recycling process, and has the advantages of simple process and low cost, which is suitable for mass production, and the positive and negative electrode materials obtained are high in purity and less in impurities; 2. In particular, the present application optimizes the types and contents of cations and anions in the eutectic salt, using Li + Ensure that there is sufficient lithium source for structural repair of failed positive electrode materials during the recycling process, and NO 3 - It can convert the lithium in the electrolyte, SEI, dead lithium and other substances remaining on the graphite surface into Li +, making full use of the residual lithium source to transform it into an external lithium replenisher for the failed positive electrode material and filling it into the lattice of the failed positive electrode material, thereby realizing the separation and regeneration of the positive and negative electrode materials of the waste lithium-ion battery simultaneously and reducing the addition of additional lithium replenishers. The entire process greatly simplifies the recycling process of the positive and negative electrode materials of waste lithium-ion batteries; 3. In addition, experiments have found that the negative electrode material does not wet the eutectic salt, so the negative electrode material floating on the surface of the molten salt is in the form of loose particles. Therefore, the present application adopts airflow suction combined with filtration to collect the regenerated negative electrode material, which has the advantages of simple process and low cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a flow chart of a method for recycling positive and negative electrode materials of waste lithium-ion batteries provided in an embodiment of the present application; Figure 2 It is a schematic diagram of a waste lithium-ion battery positive and negative electrode material recovery device provided in an embodiment of the present application.
[0019] Throughout the drawings, the same reference numerals are used to denote the same elements or structures, wherein: 1-separation unit, 2-transport pipeline, 3-collection chamber, 4-filter membrane, 5-suction pump. DETAILED DESCRIPTION
[0020] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0021] like Figure 1 As shown, according to one aspect of the present application, a method for recycling positive and negative electrode materials of waste lithium-ion batteries is provided, which specifically includes: S1 pre-treats waste lithium-ion batteries to obtain a mixed material of positive electrode materials and negative electrode materials, and then mixes the mixed material with eutectic salt to obtain a mixture to be separated. The eutectic salt is a mixture of two or more salt substances. The temperature of its eutectic point is lower than the melting point of a single salt, generally between 150℃ and 400℃, and the density of the eutectic salt is 2.5g / cm 3 ~3.5g / cm 3 In the range of , between the density of the positive electrode material and the negative electrode material; S2 heats the mixture to be separated to above the eutectic point of the eutectic salt. Due to the density of the negative electrode material (2.2 g / cm 3 ~2.4g / cm 3 ) is less than the density of the eutectic salt and will float. The density of the positive electrode material (3.6g / cm 3The solid matter in the upper layer is collected to obtain the regenerated negative electrode material, and the solid matter in the lower layer is collected to obtain the regenerated positive electrode material, thereby realizing the recycling of the positive and negative electrode materials of waste lithium-ion batteries.
[0022] The recycling method provided in the present application does not require the separation of the positive and negative electrode materials in the crushing stage. The positive and negative electrode materials of waste lithium-ion batteries can be separated by using only a eutectic salt with a density between that of the positive electrode material and the negative electrode material. This opens up a new recycling and regeneration technology route from "material" directly to "material", effectively simplifies the recycling process, and has the advantages of simple process and low cost, is suitable for mass production, and the positive and negative electrode materials obtained respectively have high purity and few impurities.
[0023] Furthermore, the cations in the eutectic salt include 5% to 35% Li + , Li + The content of lithium ions should not be less than 5% to ensure that there is sufficient lithium source for structural repair of failed positive electrode materials, and should not be higher than 35% to ensure that the lower limit of the density of the eutectic salt system is higher than 2.5 g / cm 3 ; The anions in the eutectic salt include more than 15% NO 3 - , can completely remove the impurities remaining on the graphite surface and reduce the melting point of the eutectic salt system. Specifically, due to the NO 3 - The oxidation reaction can convert the lithium in the electrolyte, SEI, dead lithium and other substances remaining on the graphite surface into Li + , so that the external lithium replenisher used as the failed positive electrode material is filled into the lattice of the failed positive electrode material, thereby simultaneously realizing the separation and regeneration of the positive and negative electrode materials and reducing the addition of additional lithium replenisher.
[0024] By optimizing the types and contents of cations and anions in the eutectic salt, the present application can realize the simultaneous recovery and regeneration of positive and negative electrode materials of waste lithium-ion batteries. Compared with the process method of performing separation and regeneration separately in the prior art, the recovery process is further simplified, the recovery cost is reduced, and there is a prospect for large-scale industrial promotion.
[0025] Furthermore, in step S1, the waste lithium-ion battery is pre-treated specifically as follows: the waste lithium-ion battery is crushed and then heated at 300°C to 450°C for 0.5h to 1h, thereby degrading the binder in the electrode sheet, separating the active material from the current collector, and then screening out the sheet materials with a size greater than 20μm such as the battery shell, the diaphragm, and the current collector to obtain a mixed material of the positive electrode material and the negative electrode material. No additional pre-treatment process is required, and the positive and negative electrode materials of waste lithium-ion batteries can be recycled by only using conventional pre-treatment methods in conjunction with subsequent processes.
[0026] Furthermore, in step S2, the negative electrode material does not wet the eutectic salt, so the negative electrode material floating on the surface of the molten salt is in the form of loose particles. With the help of the air suction and filtering device, the floating negative electrode material is continuously collected by air flow suction and filtration, so that the positive and negative electrode mixed materials can be accurately separated to obtain pure positive and negative electrode materials. At the same time, due to the non-wetting characteristics of the negative electrode material and the eutectic salt, the separation of the negative electrode material is very convenient, efficient and simple.
[0027] Furthermore, the cations in the eutectic salt also include 35% to 70% of density regulating cations, which are used to adjust the density range of the eutectic salt system to meet the separation requirements, and the rest are melting point regulating cations. + When the content of the density regulating cation reaches 100%, other cations may not be contained. Preferably, the density regulating cation includes Cs + , Ba 2 + One or more of alkali metals or alkaline earth metals with an atomic number greater than 40, the melting point regulating cations including K + , Ca 2 + One or more alkali metal or alkaline earth metal ions with an atomic number less than 21. The anions in the eutectic salt also include Br - ,I - OH - , ClO 4 - The reason why alkali metal and alkaline earth metal ions are preferred is that the outermost electron layers of the two metals have only 1 and 2 electrons, respectively, and the resulting salts are relatively stable, have less valence change, and are not easily decomposed by heat, thereby reducing the occurrence of additional side reactions.
[0028] Furthermore, the mass proportion of the co-molten salt in the mixture to be separated is greater than 2 / 3, so as to achieve a better separation effect of the positive and negative electrode materials.
[0029] Furthermore, the regenerated negative electrode material is washed with deionized water 2 to 3 times and then placed in an inert atmosphere, and annealed at 700° C. to 900° C. for 1 h to 2 h to repair a small amount of structural defects inside the graphite, thereby improving the charge and discharge cycle stability of the regenerated negative electrode material.
[0030] Furthermore, the regenerated positive electrode material is washed with deionized water for 2 to 3 times and then placed in an oxygen-containing atmosphere (air atmosphere or pure oxygen atmosphere) or an inert atmosphere (argon atmosphere), and annealed at 800°C to 950°C for 4 to 8 hours to eliminate residual lithium salts on the surface of the failed positive electrode material during the water washing process, while stabilizing the crystal structure of the regenerated positive electrode material to improve the charge and discharge cycle stability.
[0031] According to another aspect of the present application, a regenerated negative electrode material and / or a regenerated positive electrode material prepared by the above-mentioned recycling method is provided.
[0032] In the method for recycling and utilizing positive and negative electrode materials of waste lithium-ion batteries provided in the present application, the positive electrode material of the lithium-ion battery is a ternary material or / and a lithium cobalt oxide material or / and a lithium iron phosphate material, and the negative electrode material is graphite.
[0033] The chemical formula of the ternary material is: LiNi 1-x-y Co x Mn y O 2 , 0<x<1, 0<y<1, 1-xy:x:y is 1:1:1, 4:2:4, 5:2:3, 6:2:2 or 8:1:1; The chemical formula of lithium cobalt oxide material is: LiCoO 2 .
[0034] The chemical formula of lithium cobalt oxide material is: LiFePO 4 .
[0035] According to another aspect of this application, Figure 2 As shown, a recycling device for positive and negative electrode materials of waste lithium-ion batteries is provided, and the recycling device includes a separation unit 1 and a negative electrode collection unit. The separation unit 1 is used to contain a mixture to be separated obtained by mixing the positive and negative electrode materials of waste lithium-ion batteries with a eutectic salt, and to heat the mixture to be separated to above the eutectic point of the eutectic salt, so that the regenerated negative electrode material floats and the regenerated positive electrode material sinks; The negative electrode collection unit includes a transport pipe 2, a collection bin 3, a filter membrane 4 and an air pump 5. The front end of the transport pipe 2 extends into the separation unit 1 and is located above the liquid surface, and the rear end thereof extends into the collection bin 3. The front end adopts a narrow mouth mode to improve suction. The filter membrane 4 is fixed at the upper outlet position in the collection bin 3. The air pump 5 is placed above the collection bin 3 and connected to the collection bin 3 through a pipe, so that the air pump 5 generates suction, and the floating regenerated negative electrode material is sent to the collection bin 3 through the transport pipe 2 for collection by air flow suction. The tail of the transport pipe 2 is below the filter membrane 4, and the suction port of the air pump 5 is inside the filter membrane 4. With the help of suction, the negative electrode material is filtered and enriched in the collection bin 3 at the left and right ends. The advantage of this design is that it can prevent the filter membrane 4 from being blocked and achieve long-term operation.
[0036] The technical solution provided in this application is further described below based on specific embodiments.
[0037] Example 1 The performance failure of the positive electrode is LiNi 0.5 Co 0.2 Mn 0.3 O 2 The battery with graphite as the negative electrode (abbreviated as NCM523) material was crushed. The crushed battery fragments were washed with deionized water for 1-3 times to remove the electrolyte. After washing, the battery fragments were filtered and collected, and then treated at 300°C for 1h to screen out the flaky materials with a particle size greater than 20μm such as battery shells, separators, and current collectors to obtain a powder mixture of NCM523 and graphite.
[0038] The fragment mixture obtained above was mixed evenly with a eutectic salt of lithium nitrate, cesium nitrate and potassium nitrate in a mass ratio of 1:3 to obtain a mixture to be separated. The molar content ratio of lithium nitrate, cesium nitrate and potassium nitrate in the eutectic salt was 1:2:1. At this ratio, the density of the eutectic salt was 2.84 g / cm 3 .
[0039] The mixture to be separated is heated to 150°C, at which the eutectic salt melts. Since graphite and the eutectic salt are not wettable, the graphite floats on the surface of the eutectic salt and is in the form of loose powder. At this time, the graphite floating on the surface is continuously sucked into the collection bin for enrichment using a suction device. After the graphite is completely collected, the molten salt is poured out to collect the NCM523 settled at the bottom, and the poured molten salt is collected and retained for the next operation.
[0040] The dispersed NCM523 and graphite were washed twice with deionized water. After drying, NCM523 was annealed at 900℃ for 4h in an oxygen atmosphere to remove the residual lithium compounds (such as lithium carbonate) formed on the surface of the material during the water washing process. Graphite was annealed at 800℃ for 2h in an argon atmosphere to eliminate a small amount of structural defects inside the graphite structure. Finally, NCM523 positive electrode materials and graphite negative electrode materials that can be put into commercial use again were obtained.
[0041] Example 2 The performance failure of the positive electrode is LiNi 0.6 Co 0.2 Mn 0.2 O 2 The battery with graphite as the negative electrode (abbreviated as NCM622) material was crushed. The crushed battery fragments were washed with deionized water for 1-3 times to remove the electrolyte. After washing, the battery fragments were filtered and collected, and then treated at 450°C for 0.5h to screen out the flaky materials with a particle size greater than 20μm such as battery shells, diaphragms, and current collectors, and finally a powder mixture of NCM622 and graphite was obtained.
[0042] The fragment mixture obtained above was mixed evenly with a eutectic salt of lithium hydroxide, potassium nitrate and barium nitrate in a mass ratio of 1:5 to obtain a mixture to be separated. The molar content ratio of lithium nitrate, cesium nitrate and potassium nitrate in the eutectic salt was 1:5:6. At this ratio, the density of the eutectic salt was 3.05 g / cm 3 .
[0043] The mixture to be separated is heated to 300°C, at which the eutectic salt melts. Since graphite and the eutectic salt are not wettable, the graphite floats on the surface of the eutectic salt and is in the form of loose powder. At this time, the graphite floating on the surface is continuously sucked into the collection bin for enrichment using a suction device. After the graphite is completely collected, the molten salt is poured out to collect the NCM622 settled at the bottom, and the poured molten salt is collected and retained for the next operation.
[0044] The dispersed NCM622 and graphite were washed twice with deionized water. After drying, NCM622 was annealed at 850 ° C for 6 h in an oxygen atmosphere to remove the residual lithium compounds (such as lithium carbonate) produced on the surface of the material during the water washing process. Graphite was annealed at 850 ° C for 1 h in an argon atmosphere to eliminate a small amount of structural defects inside the graphite structure. Finally, NCM622 positive electrode materials and graphite negative electrode materials that can be put into commercial use again were obtained.
[0045] Example 3 The performance failure of the positive electrode is LiNi 0.8 Co 0.1 Mn 0.1 O 2The battery with graphite as the negative electrode (abbreviated as NCM811) material was crushed. The crushed battery fragments were washed with deionized water for 1-3 times to remove the electrolyte. After washing, the battery fragments were filtered and collected, and then treated at 350°C for 1 h to screen out the flaky materials with a particle size greater than 20μm such as the battery shell, separator, and current collector to obtain a powder mixture of NCM811 and graphite.
[0046] The fragment mixture obtained above was mixed evenly with a eutectic salt of lithium bromide, cesium nitrate and calcium nitrate in a mass ratio of 1:3 to obtain a mixture to be separated. The molar content ratio of lithium bromide, cesium nitrate and calcium nitrate in the eutectic salt is 3:5:1. At this ratio, the density of the eutectic salt is 3.25 g / cm 3 .
[0047] The mixture to be separated is heated to 350°C, at which the eutectic salt melts. Since graphite and the eutectic salt are not wettable, the graphite floats on the surface of the eutectic salt and is in the form of loose powder. At this time, the graphite floating on the surface is continuously sucked into the collection bin for enrichment using a suction device. After the graphite is completely collected, the molten salt is poured out to collect the NCM811 settled at the bottom, and the poured molten salt is collected and retained for the next operation.
[0048] The dispersed NCM811 and graphite were washed twice with deionized water. After drying, NCM811 was annealed at 800℃ for 6h in an oxygen atmosphere to remove the residual lithium compounds (such as lithium carbonate) produced on the surface of the material during the water washing process. Graphite was annealed at 700℃ for 2h in an argon atmosphere to eliminate a small amount of structural defects inside the graphite structure. Finally, the ternary 811 positive electrode material and graphite negative electrode material that can be put into commercial use again were obtained.
[0049] Example 4 The performance failure of the positive electrode is LiC O O 2 The battery with graphite as the negative electrode is crushed. The crushed battery fragments are washed with deionized water for 1-3 times to remove the electrolyte. After washing, the battery fragments are filtered and collected, and then treated at 450°C for 0.5 h to screen out the flaky materials with a particle size greater than 20μm such as the battery shell, diaphragm, and current collector to obtain a powder mixture of LCO and graphite.
[0050] The fragment mixture obtained above was mixed evenly with the eutectic salt of lithium bromide and cesium nitrate in a mass ratio of 1:4 to obtain a mixture to be separated. The molar content ratio of lithium bromide to cesium nitrate in the eutectic salt was 1:2. At this ratio, the density of the eutectic salt was 3.32 g / cm 3 .
[0051] The mixture to be separated is heated to 320°C, at which the eutectic salt melts. Since graphite and the eutectic salt are not wettable, the graphite floats on the surface of the eutectic salt and is in the form of loose powder. At this time, the graphite floating on the surface is continuously sucked into the collection bin for enrichment using a suction device. After the graphite is completely collected, the molten salt is poured to collect the LCO settled at the bottom, and the poured molten salt is collected and retained for the next operation.
[0052] The dispersed LCO and graphite were washed twice with deionized water. After drying, LCO was annealed at 950 ° C for 6 h in an oxygen atmosphere to remove the residual lithium compounds (such as lithium carbonate) produced on the surface of the material during the water washing process. Graphite was annealed at 800 ° C for 1 h in an argon atmosphere to eliminate a small amount of structural defects inside the graphite structure. Finally, LCO positive electrode materials and graphite negative electrode materials that can be put into commercial use again were obtained.
[0053] Example 5 The performance failure of the positive electrode is LiNi 0.5 Co 0.2 Mn 0.3 O 2 The battery with graphite as the negative electrode (abbreviated as NCM523) material was crushed. The crushed battery fragments were washed with deionized water for 1-3 times to remove the electrolyte. After washing, the battery fragments were filtered and collected, and then treated at 300°C for 1h to screen out the flaky materials with a particle size greater than 20μm such as battery shells, separators, and current collectors to obtain a powder mixture of NCM523 and graphite.
[0054] The fragment mixture obtained above was mixed evenly with the eutectic salt of lithium nitrate and cesium perchlorate in a mass ratio of 1:3 to obtain a mixture to be separated. The molar content ratio of lithium nitrate to cesium perchlorate in the eutectic salt was 1:4. At this ratio, the density of the eutectic salt was 3.02 g / cm 3 .
[0055] The mixture to be separated is heated to 180°C, at which the eutectic salt melts. Since graphite and the eutectic salt are not wettable, the graphite floats on the surface of the eutectic salt and is in the form of loose powder. At this time, the graphite floating on the surface is continuously sucked into the collection bin for enrichment using a suction device. After the graphite is completely collected, the molten salt is poured out to collect the NCM523 settled at the bottom, and the poured molten salt is collected and retained for the next operation.
[0056] The dispersed NCM523 and graphite were washed twice with deionized water. After drying, NCM523 was annealed at 900℃ for 4h in an oxygen atmosphere to remove the residual lithium compounds (such as lithium carbonate) produced on the surface of the material during the water washing process. Graphite was annealed at 800℃ for 2h in an argon atmosphere to eliminate a small amount of structural defects inside the graphite structure. Finally, NCM523 positive electrode materials and graphite negative electrode materials that can be put into commercial use again were obtained.
[0057] Example 6 The performance failure of the positive electrode is LiNi 0.5 Co 0.2 Mn 0.3 O 2 The battery with graphite as the negative electrode (abbreviated as NCM523) material is crushed. The crushed battery fragments are washed with deionized water for 1-3 times to remove the electrolyte. After washing, the battery fragments are collected by filtration and then treated at 300°C for 1h to screen out the flaky materials with a particle size greater than 20μm such as battery shells, separators, and current collectors to obtain a powder mixture of NCM523 and graphite.
[0058] The fragment mixture obtained above was mixed evenly with the eutectic salt of lithium nitrate and cesium hydroxide in a mass ratio of 1:4 to obtain a mixture to be separated. The molar content ratio of lithium nitrate and cesium hydroxide in the eutectic salt was 1:3. At this ratio, the density of the eutectic salt was 2.92 g / cm 3 .
[0059] The mixture to be separated is heated to 320°C, at which the eutectic salt melts. Since graphite and the eutectic salt are not wettable, the graphite floats on the surface of the eutectic salt and is in the form of loose powder. At this time, the graphite floating on the surface is continuously sucked into the collection bin for enrichment using a suction device. After the graphite is completely collected, the molten salt is poured out to collect the NCM523 settled at the bottom, and the poured molten salt is collected and retained for the next operation.
[0060] The dispersed NCM523 and graphite were washed twice with deionized water. After drying, NCM523 was annealed at 900℃ for 4h in an oxygen atmosphere to remove the residual lithium compounds (such as lithium carbonate) produced on the surface of the material during the water washing process. Graphite was annealed at 800℃ for 2h in an argon atmosphere to eliminate a small amount of structural defects inside the graphite structure. Finally, NCM523 positive electrode materials and graphite negative electrode materials that can be put into commercial use again were obtained.
[0061] Example 7 The battery with failed performance, whose positive electrode is made of lithium iron phosphate (LFP) material and negative electrode is graphite, is crushed. The crushed battery fragments are washed with deionized water 1-3 times to remove the electrolyte. After washing, the battery fragments are filtered and collected, and then treated at 300℃ for 1h, and then the flaky materials with a particle size greater than 20μm such as battery shell, diaphragm, current collector, etc. are screened to obtain a powder mixture of LFP and graphite.
[0062] The fragment mixture obtained above was mixed evenly with the eutectic salt of lithium bromide and cesium nitrate in a mass ratio of 1:4 to obtain a mixture to be separated. The molar content ratio of lithium bromide to cesium nitrate in the eutectic salt was 1:5. At this ratio, the density of the eutectic salt was 3.35 g / cm 3 .
[0063] The mixture to be separated is heated to 280°C, at which the eutectic salt melts. Since graphite and the eutectic salt are not wettable, the graphite floats on the surface of the eutectic salt and is in the form of loose powder. At this time, the graphite floating on the surface is continuously sucked into the collection bin for enrichment using a suction device. After the graphite is completely collected, the molten salt is poured out to collect the LFP settled at the bottom, and the poured molten salt is collected and retained for the next operation.
[0064] The dispersed LFP and graphite were washed twice with deionized water. After drying, the LFP was annealed at 800 ° C for 2 h in a hydrogen-argon mixed gas atmosphere to remove the residual lithium compounds (such as lithium carbonate) produced on the surface of the material during the water washing process. The graphite was annealed at 800 ° C for 2 h in an argon atmosphere to eliminate a small amount of structural defects inside the graphite structure. Finally, LFP positive electrode materials and graphite negative electrode materials that can be put into commercial use again were obtained.
[0065] Example 8 The performance failure of the positive electrode is LiNi 0.5 Co 0.2 Mn 0.3 O 2 The battery with graphite as the negative electrode (abbreviated as NCM523) material was crushed. The crushed battery fragments were washed with deionized water for 1-3 times to remove the electrolyte. After washing, the battery fragments were filtered and collected, and then treated at 300°C for 1h to screen out the flaky materials with a particle size greater than 20μm such as battery shells, separators, and current collectors to obtain a powder mixture of NCM523 and graphite.
[0066] The fragment mixture obtained above was mixed evenly with the eutectic salt of lithium bromide and potassium bromide in a mass ratio of 1:3 to obtain a mixture to be separated. The molar content ratio of lithium bromide to potassium bromide in the eutectic salt is 3:2. At this ratio, the density of the eutectic salt is 3.15 g / cm 3 .
[0067] The mixture to be separated is heated to 480°C, at which the eutectic salt melts. Since graphite and the eutectic salt are not wettable, the graphite floats on the surface of the eutectic salt and is in the form of loose powder. At this time, the graphite floating on the surface is continuously sucked into the collection bin for enrichment using a suction device. After the graphite is completely collected, the molten salt is poured out to collect the NCM523 settled at the bottom, and the poured molten salt is collected and retained for the next operation.
[0068] The dispersed NCM523 and graphite were washed twice with deionized water. After drying, NCM523 was annealed at 900℃ for 4h in an oxygen atmosphere to remove the residual lithium compounds (such as lithium carbonate) produced on the surface of the material during the water washing process. Graphite was annealed at 800℃ for 2h in an argon atmosphere to eliminate a small amount of structural defects inside the graphite structure. Finally, NCM523 positive electrode materials and graphite negative electrode materials that can be put into commercial use again were obtained.
[0069] Example 9 The performance failure of the positive electrode is LiNi 0.5 Co 0.2 Mn 0.3 O 2 The battery with graphite as the negative electrode (abbreviated as NCM523) material was crushed. The crushed battery fragments were washed with deionized water for 1-3 times to remove the electrolyte. After washing, the battery fragments were filtered and collected, and then treated at 300°C for 1h to screen out the flaky materials with a particle size greater than 20μm such as battery shells, separators, and current collectors to obtain a powder mixture of NCM523 and graphite.
[0070] The fragment mixture obtained above was mixed evenly with a eutectic salt of lithium bromide, lithium fluoride and lithium chloride in a mass ratio of 1:4 to obtain a mixture to be separated. The molar content ratio of lithium bromide, lithium fluoride and lithium chloride in the eutectic salt is 2:3:2. At this ratio, the density of the eutectic salt is 3.1 g / cm 3 .
[0071] The mixture to be separated is heated to 450°C, at which the eutectic salt melts. Since graphite and the eutectic salt are not wettable, the graphite floats on the surface of the eutectic salt and is in the form of loose powder. At this time, the graphite floating on the surface is continuously sucked into the collection bin for enrichment using a suction device. After the graphite is completely collected, the molten salt is poured out to collect the NCM523 settled at the bottom, and the poured molten salt is collected and retained for the next operation.
[0072] The dispersed NCM523 and graphite were washed twice with deionized water. After drying, NCM523 was annealed at 900℃ for 4h in an oxygen atmosphere to remove the residual lithium compounds (such as lithium carbonate) produced on the surface of the material during the water washing process. Graphite was annealed at 800℃ for 2h in an argon atmosphere to eliminate a small amount of structural defects inside the graphite structure. Finally, NCM523 positive electrode materials and graphite negative electrode materials that can be put into commercial use again were obtained.
[0073] Example 10 The performance failure of the positive electrode is LiNi 0.3 Co 0.3 Mn 0.3 O 2 The battery with graphite as the negative electrode is crushed. The crushed battery fragments are washed with deionized water for 1-3 times to remove the electrolyte. After washing, the battery fragments are filtered and collected, and then treated at 300°C for 1h to screen out the flaky materials with a particle size greater than 20μm such as battery shells, separators, and current collectors to obtain a powder mixture of NCM333 and graphite.
[0074] The fragment mixture obtained above was mixed evenly with a eutectic salt of lithium nitrate, cesium nitrate and potassium nitrate in a mass ratio of 1:3 to obtain a mixture to be separated. The molar content ratio of lithium nitrate, cesium nitrate and potassium nitrate in the eutectic salt was 1:2:1. At this ratio, the density of the eutectic salt was 2.84 g / cm 3 .
[0075] The mixture to be separated is heated to 150°C, at which the eutectic salt melts. Since graphite and the eutectic salt are not wettable, the graphite floats on the surface of the eutectic salt and is in the form of loose powder. At this time, the graphite floating on the surface is continuously sucked into the collection bin for enrichment using a suction device. After the graphite is completely collected, the molten salt is poured out to collect the NCM333 settled at the bottom, and the poured molten salt is collected and retained for the next operation.
[0076] The dispersed NCM333 and graphite were washed twice with deionized water. After drying, NCM333 was annealed at 900℃ for 4h in air atmosphere to remove the residual lithium compounds (such as lithium carbonate) formed on the surface of the material during the water washing process. Graphite was annealed at 800℃ for 2h in argon atmosphere to eliminate a small amount of structural defects inside the graphite structure. Finally, NCM333 positive electrode material and graphite negative electrode material that can be put into commercial use again were obtained.
[0077] Embodiment 11 The performance failure of the positive electrode is LiNi 0.5 Co 0.2 Mn 0.3 O 2The battery with graphite as the negative electrode (abbreviated as NCM523) material was crushed. The crushed battery fragments were washed with deionized water for 1-3 times to remove the electrolyte. After washing, the battery fragments were filtered and collected, and then treated at 300°C for 1h to screen out the flaky materials with a particle size greater than 20μm such as battery shells, separators, and current collectors to obtain a powder mixture of NCM523 and graphite.
[0078] The fragment mixture obtained above was mixed evenly with lithium bromide in a mass ratio of 1:3 to obtain a mixture to be separated. The density of lithium bromide molten salt is 3.46 g / cm 3 .
[0079] The mixture to be separated is heated to 480°C, at which temperature lithium bromide melts. Since the graphite floating on the surface is wettable with lithium bromide molten salt, it is difficult to collect it by suction. In this case, the floating graphite is filtered and collected by continuous salvage using a screen. After the graphite is completely collected, the molten salt is poured to collect the NCM523 material settled at the bottom, and the poured molten salt is collected and retained for the next operation.
[0080] The dispersed NCM523 and graphite were washed twice with deionized water. After drying, NCM523 was annealed at 900℃ for 4h in an oxygen atmosphere to remove the residual lithium compounds (such as lithium carbonate) produced on the surface of the material during the water washing process. Graphite was annealed at 800℃ for 2h in an argon atmosphere to eliminate a small amount of structural defects inside the graphite structure. Finally, NCM523 positive electrode materials and graphite negative electrode materials that can be put into commercial use again were obtained.
[0081] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
Claims
1. A method for recycling positive and negative electrode materials of waste lithium-ion batteries, characterized in that: Specifically include: S1 pre-treats the waste lithium-ion battery to obtain a mixed material of positive electrode material and negative electrode material, and then mixes the mixed material with a eutectic salt to obtain a mixture to be separated, wherein the density of the eutectic salt is 2.5 g / cm 3 ~3.5g / cm 3 within the scope of S2: heating the mixture to be separated to above the eutectic point of the eutectic salt, collecting the upper solid material to obtain the regenerated negative electrode material, and collecting the lower solid material to obtain the regenerated positive electrode material.
2. The recycling method according to claim 1, characterized in that: According to the molar content, the cations in the eutectic salt include 5% to 35% of Li + The anions in the eutectic salt include more than 15% NO3 - .
3. The recycling method according to claim 1, characterized in that: The regenerated negative electrode material is collected by air flow suction combined with filtration.
4. The recycling method according to claim 1, characterized in that: In step S1, the waste lithium-ion batteries are pre-treated by crushing the waste lithium-ion batteries and heating them at 300°C to 450°C for 0.5h to 1h, and then screening out flake materials with a size greater than 20μm to obtain a mixed material of positive electrode materials and negative electrode materials.
5. The recycling method according to claim 2, characterized in that: According to the molar content, the cations in the eutectic salt also include 35% to 70% of density regulating cations, and the rest are melting point regulating cations, wherein the density regulating cations are alkali metals or alkaline earth metal ions with an atomic number greater than 40, and the melting point regulating cations are alkali metals or alkaline earth metal ions with an atomic number less than 21; the anions in the eutectic salt also include Br - ,I - OH - 、ClO4 - One or more of .
6. The recycling method according to claim 1, characterized in that: The mass proportion of the co-molten salt in the mixture to be separated is greater than 2 / 3.
7. The recovery method according to any one of claims 1 to 6, characterized in that: The regenerated negative electrode material is washed and placed in an inert atmosphere, and annealed at 700° C. to 900° C. for 1 h to 2 h to improve the charge and discharge cycle stability of the regenerated negative electrode material.
8. The recovery method according to any one of claims 1 to 6, characterized in that: After cleaning, the regenerated positive electrode material is placed in an oxygen-containing atmosphere or an inert atmosphere, and annealed at 800° C. to 950° C. for 4 h to 8 h to improve the charge and discharge cycle stability of the regenerated positive electrode material.
9. Regenerated negative electrode material and / or regenerated positive electrode material prepared by the recycling method according to any one of claims 1 to 8.
10. A device for recovering positive and negative electrode materials of waste lithium-ion batteries, characterized in that: The recycling device comprises a separation unit (1) and a negative electrode collection unit, wherein the separation unit (1) is used to contain a mixture to be separated obtained by mixing positive and negative electrode materials of waste lithium-ion batteries with a eutectic salt, and to heat the mixture to be separated to a temperature above the eutectic point of the eutectic salt, so that the regenerated negative electrode material floats and the regenerated positive electrode material sinks; The negative electrode collection unit comprises a transport pipe (2), a collection bin (3), a filter membrane (4) and an air suction pump (5); one end of the transport pipe (2) extends into the separation unit (1) and is located above the liquid surface, and the other end of the transport pipe (2) extends into the collection bin (3); the outlet of the collection bin (3) is provided with a filter membrane (4); the air suction pump (5) is connected to the outlet of the collection bin (3), and the suction port of the air suction pump (5) is located in the internal space of the filter membrane (4), so that the regenerated negative electrode material that is not infiltrated with the eutectic salt and floats on the surface is collected by air suction.
Citation Information
Patent Citations
Method for recovering lithium ion battery wastes by using thermal cracking
CN106941198A
Square-section liquid metal battery provided with fluid instability suppression grid device
CN109786862A
Air flotation method for separating carbon material in molten salt
CN114477133A
Method for repairing negative electrode graphite of lithium manganate battery by plasma
CN115602950A
Recycling and repairing method of lithium ion battery and battery
CN116581412A
Cited By
Method for producing a rechargeable battery using spent cathode active material
DE102025115194B3
Method and apparatus for recycling positive and negative electrode materials of spent lithium-ion battery, and product
WO2026129651A1